Safety and efficacy of Tobramycin 0.3% + Fluormetholone 0.1% (eye drops) fixed combination as a preoperative preparation and postoperative management of patients with wet AMD after intravitreal injection of ranibizumab. An observational, noncomparative single-center study - V.P. Fokin; S.V. Balalin; L.I. Ushakova (Офтальмохирургия)
Purpose. To evaluate safety and efficacy of Floas-T® (Tobramycin 0.3% + Fluormetholone 0.1%) as a preoperative preparation and postoperative management of patients with wet form of age-related macular degeneration (AMD) before and after intravitreal injection (IVI) of anti-VEGF drugs. Material and methods. 50 patients (50 eyes) with the wet form of AMD were examined and divided into two groups. The first group included 32 patients (32 eyes) with wet form of AMD. The second group consisted of 18 patients (18 eyes) with primary (11 eyes) and advanced (7 eyes) stages of primary open angle glaucoma with normalized IOP and wet form of AMD. Results. There were no significant changes in ВСVA and tonometric IOP values in the two groups before and within 7 days after IVI of ranibizumab and Floas-T® instillations. Average value of individually tolerable true IOP in patients of the second group was 16,3±1,1 mm Hg, while average value of initial true IOP (14,7±2,56 mm Hg) pre-op was lower than tolerable pressure, indicating that individual norm of ophthalmotonus in glaucoma patients was reached. The difference between the mean values of ocular hydrodynamics in both groups before and 1 week after surgery was also statistically unsignificant (p>0.05). The difference between the mean values of the Schirmer I test was statistically unsignificant in patients in the two groups (p>0.05) before and after surgery, indicating the absence of Floas-T® effect on tear production. There were no local and systemic side effects of Floas-T® in 50 patients (50 eyes) during the observation period. Conclusion. Floas-T® had an anti-inflammatory effect without a decrease in the aqueous humor outflow, did not cause a significant increase in IOP in the early postoperative period, did not decrease tear production, and did not cause adverse local and systemic side effects. Floas-T® can be used as a preoperative preparation and postoperative management drug in patients with wet type of AMD as well as in combination with primary open angle glaucoma when achieving an individual level of intraocular pressure.